Analisis Kebijakan Luar Negeri Rusia: Pembangunan Pangkalan Militer di Laut Merah 2020-2025 - Nahar Maulana Maarif; Jiehan Pratama Saksananta; Shakira Adriana Handriza; Prihandono Wibowo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Russia's plan to establish a military base in the Red Sea region through the coast of Sudan is one of the geopolitical and foreign policy developments in international dynamics experiencing a significant surge. Since the meeting between then Sudanese President Omar Al-Bashir and Russian President Vladimir Putin in Sochi in November 2017, Russia's aspirations in the Red Sea region have increased. Russia has continued its efforts to penetrate the Red Sea region in various ways, seeking logistical and legal loopholes, forming alliances with countries such as Turkey, and putting pressure on the Gulf states, especially Saudi Arabia, while exploiting and complicating the situation. To analyze the dynamics of Russian foreign policy in the Red Sea, the author uses the Foreign Policy Decision Making Theory proposed by William D. Coplin in his work entitled “Foreign Policy Decision-making”, that in the process of formulating foreign policy, there are at least three basic factors that are taken into consideration by policy makers Domestic Politics, Economic and Military Capability, and International Context. In making this decision, the Russian President considered several things such as positive support from domestic policy influencers, Russia's economic independence, and the presence of the Russian military, either under Wagner or the Ministry of Defense in Sudan. With the inauguration of the construction of Russian military bases in Sudan, Russia can expand its geopolitical influence in the Red Sea region, in line with its foreign policy objectives to create a balance of power with Western powers in the Middle East.